YVO4:RE (RE = Eu, Tm, and Yb/Er) nanoparticles synthesized by the microwave-assisted hydrothermal method for photoluminescence application - Pinatti, Ivo Mateus; de Foggi, Camila Cristina; Teodoro, Marcio Daldin; Longo, Elson; Simões, Alexandre Zirpoli; Rosa, Ieda Lúcia Viana (Eclética Química, 2022)
Here, an experimental study is presented on the YVO4:RE (RE = Eu, Tm, and Yb/Er) nanoparticles synthesized by means of the microwave-assisted hydrothermal method. Different characterization techniques (X-ray diffraction, Raman and ultraviolet-visible spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, and photoluminescence emissions) have been employed to examine the structural, optical, as well as its morphology and photoluminescent properties. The as-synthetized samples present different emission colors due to RE3+ ions, as well as nanosized spherical morphology because of synthesis method. These materials can be considered efficient materials for optical devices.